Articulating nurse practitioner practice using King's theory of goal attainment. Issue 11 (5th March 2015) - de Leon‐Demare, Kathleen; MacDonald, Jane; Gregory, David M.; Katz, Alan; Halas, Gayle
Abstract: Purpose: To further understand the interactions between nurse practitioners (NPs) and patients, King's nursing theory of goal attainment was applied as the conceptual framework to describe the interactions between NPs and patients in the primary care setting. Data sources: Six dyads of NPs and their patients were video‐ and audio‐taped over three consecutive clinic visits. For the purposes of this arm of the study, the audio‐taped interactions were transcribed and then coded using King's concepts in her theory of goal attainment. Conclusions: King's theory was applicable to describe NP practice. King's concepts and processes of nurse–patient interactions, such as disturbances, mutual goal setting, and transactions, were observed in NP–patient interactions. Implications for practice: Disturbances during clinical encounters were essential in the progression toward goal attainment. Elements, such as social exchange, symptom reporting, role explanation, and information around clinical processes facilitated relationship building. NPs as practitioners need to be reflective of their own practice, embrace disturbances in the clinical encounter, and attend to these as opportunities for mutual goal setting.